The benefits of a 5-day dysphagia intensive placement - Cocks, Naomi; Harding, C.; Pritchard, M. (Informa Healthcare, 2014)
Finding practical dysphagia opportunities for students pre-qualifi cation is challenging. Discussions with clinicians led to the development of a new placement model. The placement was just five days and had an accompanying workbook. The current study aimed to evaluate the benefits of the placement. Data were analysed from 40 students who attended an adult dysphagia placement and 13 who attended a paediatric dysphagia placement. Measures included a pre and post self-rating questionnaire, qualitative feedback from clinical educators and students and a pre and post measure of knowledge using concept maps. Student self-rating data indicated gains in experience, awareness, knowledge, clinical skills, competence, confidence and interest in dysphagia. Clinical educators and students also reported a range of benefits from this placement. Students who undertook a placement that focused on adult dysphagia significantly increased their knowledge of adult dysphagia, but this did not generalize to paediatric dysphagia. Despite reporting that they felt they had gained in knowledge of dysphagia, the students who did a paediatric dysphagia placement did not significantly increase their knowledge of dysphagia. The study raises a number of important considerations when designing placements including length, timing, intensity, how best to encourage generalization of knowledge, and how best to measure learning.